Reference Range of Penile Dimensions of the Adult Male and Correlation with Somatometric Parameter in a Tertiary Care Hospital of Bangladesh: A Prospective Study (KYAMC Journal, 2021)
Background: The penile size has always been a symbol of manliness and pride. Many adult think that there penile length are not adequate and goes to different medical disciplines. There is no study in Bangladesh regarding penile size and somatometric parameter. The results will help in counseling patients afraid of their penile size , also in clinical and research purpose.Objective: To assess the penile size in different dimensions such as flaccid, stretch, and girth (circumferential) penile length and its relationship with age, height, weight, and BMI.Materials and Methods: The study was conducted on 300 adult males with no penile abnormalities. Length of penises in flaccid, stretch, and circumference were measured. Age ,height, weight were measured and BMI (body mass index) was calculated. Correlation of penile dimensions with somatometric parameters were analyzed.Results: The average flaccid penile length(FPL) was 7.81 cm, the mean stretch length(SPL) was 11.21 cm, and the mean circumferential length(CPL) was 8.65 cm. The penile length in the three dimensions was significantly different from each other (p